Conceptual and Empirical Issues for Alternative Student Loan Designs: The Significance of Loan Repayment Burdens for the United States. Issue 1 (May 2017) - Chapman, Bruce; Dearden, Lorraine
In this article, we compare the two main types of student loans used to finance postsecondary education: mortgage-type loans, which are repaid over a set period of time and mainly used in the United States; and income-contingent loans, which are repaid depending on students' future income and used in Australia and England. We argue that the major concern with mortgage-type loans is the repayment burden that falls on students. Repayment burden—the proportion of a debtor's income required to repay loans—is fundamental to the assessment of student loan systems because it affects the probability of students defaulting on loan repayment, and because it bears on debtors' consumption and standard of living. We show that Stafford loans imply extremely difficult financial circumstances for a minority of U.S. loan recipients, and that income-contingent loans can solve those problems. The financial benefits of income-contingent loans are illustrated through a hypothetical student loan experience.